2017
DOI: 10.1089/pop.2016.0075
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Emergency Department Use Among Medicaid and Commercial Patients Using All-Payer All-Claims Data

Abstract: The high rate of emergency department (ED) use by Medicaid patients is not fully understood. The objective of this paper is (1) to provide context for ED service use by comparing Medicaid and commercial patients' differences across ED and non-ED health service use, and (2) to assess the extent to which Medicaid-commercial differences in ED use can be explained by observable factors in administrative data. Statistical decomposition methods were applied to ED, mental health, and inpatient care using 2011-2013 Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
5
20
2
Order By: Relevance
“…Another study looking at the use of ED among children with AD found that most ED visits were by publicly insured patients [ 52 ]. These findings corroborate those of numerous other studies, suggesting a need for improved utilization and convenient access to primary care and specialty outpatient care for Medicaid recipients [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another study looking at the use of ED among children with AD found that most ED visits were by publicly insured patients [ 52 ]. These findings corroborate those of numerous other studies, suggesting a need for improved utilization and convenient access to primary care and specialty outpatient care for Medicaid recipients [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…Emergency room claims indicated a much lower rate among our program patients, as well as reduced level of ER costs, compared to the control group. However, the rates discovered in this study were much higher than those previously reported in Quittner et al This difference could be because Quittner only included commercially insured patients, while both our program and control groups had a high proportion of managed Medicaid patients, who tend to have high ER utilization …”
Section: Discussioncontrasting
confidence: 69%
“…This differs from other studies which noted patients with public insurance were more likely to use the ED than patients with other insurance types. [17][18][19][20][21] Only 6% of our study population was uninsured and all ED utilizers had insurance, supporting other findings that lack of insurance likely is not a major factor for ED use for migraine. 4,7,22 There was no statistically significant difference in race between groups, though nonwhite race was found to be more common in ED utilizers in a Georgia study.…”
Section: We Found No Difference In Ed Utilization Between Patients Withsupporting
confidence: 84%